Latrines Problem, Defecation Behavior, and Implementation of GERBANG JASA in Murtajih Village, Pamekasan, Indonesia - Susianto, Steven Christian; Israna, Israna; Haque, Izaratul; Habibie, Melyana; Ginting, Sri Mentari Br; Anggraini, Jeni Novita (Universitas Airlangga, 2022)
Unhealthy latrines and defecation behaviors are associated with a higher diarrhea and stunting incidence. The authors developed Healthy Latrine Building Program (GERAKAN BANGUN JAMBAN SEHAT), which is was abbreviated as Gerbang Jasa, to improve latrine problems and long-term effort to prevent stunting. This study aimed to describe the latrine problems and implementation of Gerbang Jasa in Murtajih Village, Pamekasan., Indonesia This research was a descriptive study and involved all families with unhealthy or sharing latrines in Telaga Sari and Pao Gading, Murtajih. We assessed the knowledge and family characteristics through a questionnaire and collected children's height and age under five years. Thirty families were included in this study, 16 from Pao Gading and 14 from the Telaga Sari. Half of them used unhealthy latrine (cemplung) and the others shared latrines, 59% of farmer occupation and most of them had income under Rp.1.000.000,00. Meanwhile, 12 children under five years from their family was not stunted. During our movement, the authors got funds Rp 18.261.000,00 and successfully built 63,3% latrines with sept tank, 16,7% of latrines only and all the unhealthy latrines were closed by subject. Farmer occupation, family income under Rp 1.000.000,00 were the most cause of latrines problems. Meanwhile, Gerbang jasa could improve latrines problem in Murtajih Village, Pamekasan.